KEBIJAKAN LUAR NEGERI KOREA SELATAN DALAM MENYIKAPI SANKSI EKONOMI CHINA TERKAIT PENEMPATAN SISTEM PERTAHANAN TERMINAL HIGH ALTITUDE AREA DEFENSE (THAAD) - Azzahra Shafira Ananta (2022)
This study describes South Korea's foreign policy in responding to China's economic sanctions related to the deployment of the Terminal High Altitude Area Defense (THAAD) defense system. South Korea's policy of placing THAAD is a defensive policy in order to protect itself from North Korean threats, but this policy is opposed by China, which considers THAAD a threat. China imposed economic sanctions on South Korea in retaliation for South Korea's decision to place THAAD, so this research explains the efforts made by South Korea to overcome these economic sanctions. This research explains South Korea's foreign policy through the adaptive model of foreign policy by James N. Rosenau and the concept of normalization by Robert P. Barston. The method used in this research is descriptive qualitative, with data collection techniques through literature studies and interview. The results of this research explains that in response to China's economic sanctions, South Korea has adapted the foreign policy model of preservative adaptation and implemented in the form of normalizing relations between South Korea and China, and economic relations between the two countries have recovered.